New Systems for Laser Cladding. Issue 3 (2nd May 2013) - Lester, Sam; Longfield, Nick; Griffiths, Justin; Cocker, John; Staudenmaier, Christian; Broadhead, Gary
Abstract Components used in the manufacture of steel strip work in exceptionally aggressive environments and have to withstand service at high temperatures in corrosive atmospheres under mechanical wear and frequent and heavy impact loading. Conventionally, components that are subject to high wear or corrosion have often been manufactured from rich chemistry steels or hardfaced using submerged arc clad martensitic stainless steels to increase their campaign life and therefore maximise line throughput by extending maintenance intervals without any sacrifice to product quality.